Interpreting area of pinched memristor hysteresis loop. Issue 2 (1st January 2014) - Biolek, D.; Biolek, Z.; Biolková, V.
Abstract : It is shown that the area of the pinched hysteresis loop of the current‐controlled ideal memristor represents the quantity 'content', which was introduced into the theory of nonlinear systems by Millar in 1951. Two parts of the content are identified which correspond to distinct parts of the area below the v–i characteristic of the memristor: one is related to the power conditions and the other to the instantaneous state of the memristor memory. It is demonstrated for a memristor driven by the sinusoidal current that the power part of the content depends on the fundamental harmonic of the voltage, whereas the memory part of the content is given only by the higher harmonics of the voltage, and only by the even harmonics in the case of entirely closed loops. The analogous conclusions also hold for the voltage‐controlled memristor.